Study of two important medicinal plants, common sage and five flavor berries - Mohamad Hesam SHAHRAJABIAN; Wenli SUN (Notulae Scientia Biologicae, 2024)
Sage (Salvia officinalis L.) of the Lamiaceae family contains a healthy dose of vitamins, minerals and rich in several nutrients. Schisandra berry (Schisandra chinensis (Turcz.) Baill. (Magnoliaceae) or Wu-Wei-Zi, which means the fruit of five tastes, is a generally used herb in traditional Chinese medicine (TCM). The five tastes of Schisandra berry refer to its impact on the five visceral organs in the body. S. chinensis has been utilized to treat sleep disorders and a tonic for kidney and brain in traditional Chinese medicine. The five important components of S. chinensis are Schisandrol B, Schisandrin A, γ-Schisandrin, Gomisin N, and Schisandrin C. The aim of this review was to outline the most notable traditional and modern health benefits of common sage and Schisanda berries. Common sage has several promising health benefits which can be consumed fresh, dried, or as a tea. It has shown antioxidant, anti-diabetes, anti-cancer, anti-obesity, anti-cholesterol, anti-bacterial, and anti-diarrheal activities. Health benefits of S. chinensis are antimicrobial, anti-cancer, anti-obesity, anti-diabetic, and anti-aging related effects. The treatment with natural herbal medicines which are also super-fruit and non-synthetic drugs is recommended.